Perspectives of Natural Biological Resources Development of the Arctic and Northern Territories of Krasnoyarsk Krai - PARSHUKOV, Denis Victorovich; NEVZOROV, Victor Nikolayevich; YANOVA, Marina Anatolevna; OLEYNIKOVA, Elena Nikolayevna; MATSKEVICH, Igor Victorovich (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
The Arctic region and the Far North have an important strategic significance for the Russian Federation. These territories possess vast resources of mineral raw materials, as well as significant volumes of plant, water and animal resources. The industrial development of the Arctic region and the northern territories has considerable economic perspectives but it creates also external effects (externalities) for ecosystems and the local indigenous population. The purpose of this research is to determine the perspectives of the commercial development and processing of plant and animal raw materials in the areas of residence of the indigenous small-numbered peoples of the north of Krasnoyarsk Krai. The object of the research is the Arctic region and the northern territories of Krasnoyarsk Krai. The main types of plant and animal raw materials are berries, mushrooms, pine nuts, as well as meat and velvet of the reindeer. As a result of the research, the economic estimation of the operational reserves of certain types of forest edible resources was given. The potential volume of the domestic and wild reindeer velvet procurement reserve in Krasnoyarsk Krai was determined. The possible volumes of output of derivative products of plant and animal raw materials of the north of Krasnoyarsk Krai were calculated. The general estimation of the investment attractiveness of the branch was given. When revealing the perspectives of biological resources development, the main specific problems of irrational use of natural resources, access to the labor resources, institutional environment of hunting and cropping business were distinguished.